THE CORRELATION BETWEEN SATISFACTION OF ANTENATAL CARE SERVICES AND VISITS OF PREGNANT WOMEN DURING THE PANDEMI PERIOD AT PEGANTENAN PUSKESMAS, PAMEKASAN DISTRICT - Adella Eka Winanda; Endyka Erye Frety; Dewi Setyowati (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
The COVID-19 pandemic has harmed health services, one of which is a decrease in thenumber of visits. At the Pegantenan Community Health Center, Pamekasan Regency,Madura, it was 41% from 2019 with only 194 pregnant women visiting in 2021. Besides that,the regularity of ANC visits is influenced by the satisfaction of pregnant women in gettingservices. This study aims to analyze the relationship between satisfaction with antenatal careservices and visits by pregnant women during the pandemic at the Pegantenan HealthCenter. This type of research is quantitative research with a cross-sectional research design.Determination of the sample by purposive sampling technique. The research was conductedat the Pegantenan Health Center in May 2022 and 44 respondents were involved in thisstudy. Respondents were given a questionnaire to determine the variables of satisfaction withANC services and the number of visits. The statistical test used SPSS version 22 software, thetest used was chi-square with a value of ρ <0.05. Based on the research and filling out thequestionnaire that was filled in by 44 respondents in the 3rd trimester of pregnancy, 82% ofpregnant women were declared satisfied and 18% expressed dissatisfaction with antenatalcare services at the Pegantenan Health Center; 89% of pregnant women make visitsaccording to the minimum standard of antenatal care visits and 11% of pregnant women donot make visits according to the minimum standard of antenatal care visits. The results of thestudy after the chi-square analysis test was carried out, the Asymp. The Sig value was 0.000or the value of ρ <0.05. There was a correlation between satisfaction with antenatal careservices and visiting pregnant women during the pandemic at the Pegantenan Health Center.